EFEKTIVITAS SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS PENERAPAN STRATEGI PEMBELAJARAN DEEP LEARNING DI SEKOLAH DASAR ISLAM TELADAN SUCI JAKARTA - Andrianto, Krisna (UNISAN JURNAL, 2025)
Deep learning in the context of education refers not only to artificial intelligence technology, but also to an in-depth learning approach that encourages holistic, reflective, and meaningful understanding of concepts. This article aims to examine how the deep learning approach is applied in Elementary SD Islam Teladan Suci Jakarta. Through literature studies and surveys of elementary school teachers, it was found that despite the potential to improve students' conceptual understanding and critical thinking, the implementation of deep learning still faces challenges in terms of curriculum, teacher training, and supporting facilities